Antero-inferior tympanic visibility during microscopy - Munjal, Manish; Talwar, Gopika; Munjal, Shubham; Saggar, Tulika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The antero-inferior recess of the ear canal is not visible to the otologist, thereby effecting proper placement of the graft and thereby affecting its uptake .The visibility of this region in the adult population is assessed. Methods: The quadrants of tympanic membrane were examined in 60 subjects with perforated tympanic membrane undergoing tympanoplasty. The study was conducted in the department of ENT-HNS (ear, nose and throat-head and neck surgery), Dayanand Medical College and Hospital, Ludhiana. Results: With the microscope in 48 (80%) entire perforation could be visualized and in 12 (20%) margins were not in the line of view. 5 perforations were posterior superior and 12 were total perforations. Otoendoscope examination with zero degree could show the entire margin of the perforation. Conclusions: In 80% population the antero-inferior quadrant of the tympanic membrane is accessible to straight vision of the microscope.